Pendampingan Pesantren Al-Barakah Mojokerto dalam Membangun Organisasi Sehat untuk Meningkatkan Ketahanan di Era Digital - Yaqin, Ainul; Syarif, M. (Proceedings of Annual Conference on Community Engagement, 2022)
Pesantren educational institutions often experience a decline in their role in society when the founding figure dies. Apart from that, the successor of the founding figure also has the same authority and competence as that of his predecessor. If not, it is predictable that the educational institution will gradually be abandoned by the community. This happened at the Al-Barakah Pesantren Mojokerto, which was the subject of community service activities. The decline of the Al-Barakah Pesantren was caused by an internal conflict that could not be resolved. The conflict was triggered by the absence of an organizational system, including the absence of AD-ART, election regulations, employment regulations, financial regulations, regulations on wealth/assets/waqf and so on. If the Kyai is still alive, the organizational system that is not yet ideal can be covered by the Kyai's charisma, so that all components can still carry out their duties properly because they adhere to the principle of sam'an wa tha'atan. Organizational conflict is triggered by the absence of an organizational system that provides opportunities for each party to make their own interpretations, causing misunderstandings and conflicts. This destructive conflict can be minimized by providing adequate institutional systems and organizational regulations to serve as guidelines for relevant parties in carrying out their duties and authorities. Patterns of institutional management that are in line with the demands of the times are a must for an educational institution if it wants to exist and is desired by the community. Educational institutions need to develop modern, effective and efficient and participatory management. In this way, pesantren can create harmonious and communicative conditions among organizational components, so as to improve their performance and gain public trust.